As feiras livres sob a lógica do capital: da produção camponesa à subsunção do trabalho na circulação - Andrade, Sheyla Silveira (2011)
The importance of this research is to analyze the insertion of peasant production, under the capital logics in popular markets, taking as reference the liaison and the subordination/ determination the of production prices. The empirical site is the popular market in the district of Castelo Branco in Aracaju. Firstly, a return of the origins of exchange up to its processes in modernization was important, including the appearing of the popular markets in this process. Therefore, it is with the modernization that the city reproduces a permanent market and the periodical market loses its capacity of central place. In this reasoning, the two economic circuits (superior and inferior) are important to understand the functioning of the markets in the cities. Therefore, the transference of a part of peasant production to a market of closest city is an example of the way that this cultivation circulates. Then, the essential form of capital that subordinates the peasant production is the commercial type. Verified that part of the goods that circulates in the fair is of peasant origin, it is necessary to define the peasant concept. The literature about peasant production is extensive, from the reading of the classics, debates on the contradictory process of enlarged reproduction of capital would engender no capitalist production relations, up to pluriactivity. The methodology employed in the study consists in the debate to construct the peasant image as a social actor and its link with the circulation segment, beyond the field research thought participant observation and accomplishment of interviews in the market. The conclusion is that the consequences for the breaking of the self-sufficiency of systems of production prior to capitalism was very important for the capital expansion and the popular market was important in this context because it was there that man made their first exchanges and because it is included in the sphere of circulation, where peasant production has come in the form of merchandise. This comes to show that it follows the process of accumulation of wealth under capitalism, highlighting their specificities.